Pengaruh Kemiringan Lereng dan Litologi Batuan Dasar terhadap Kadar Nikel pada Endapan Nikel Laterit di Kecamatan Wolo, Kabupaten Kolaka, Sulawesi Tenggara - Lovena V.F Kenedy; Setia Pambudi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Indonesia holds the world's largest nickel resource potential, with significant reserves in Southeast Sulawesi dominated by lateritic deposits derived from ultramafic rock weathering. The research area is in Wolo District, Kolaka Regency, with prominent Ni prospect. This study evaluates the influence of slope gradient and bedrock lithology on Ni grade distribution within lateritic profiles. Methods included literature review, bedrock and core sampling, petrographic and XRF analyses, and ArcGIS–Surfer–Excel processing for spatial and boxplot-based correlation analysis. Results show that in Pit A, characterized by relatively flat morphology, the highest Ni grades (average 1.2%) occur in saprolite on gentle slopes (2–7°), where optimal infiltration and intensive peridotite weathering favor downward Ni enrichment, while limonite enrichment develops on moderate slopes (15–30°) over dunite. In contrast, Pit B, with steeper hill–mountain morphology, records peak Ni grades (average 1.4%) in limonite on steep slopes (30–70°), where dunite weathering combined with limited deep infiltration and leaching leads to preferential Ni retention in the limonite zone, and peridotite generally yields lower grades due to morphology-related less efficient Ni trapping.